Pengaruh Pemberian Ekstrak Daun Pandan Wangi (Pandanus Amarillyfolius Roxb) terhadap Berat Testis dan Diamater Tubulus Mencit (Mus Musculus) - Lili Fajria (NERS Jurnal Keperawatan)
Pandan Wangi (Pandanus amaryllifolius Roxb) is commonly used by Indonesian people. The chemical contents of pandan wangi are: tannin, saponin, alkaloid, flavonoid, and color essence (DepKes RI, 1997). According to some research on other vegetation such as star fruit (Rezano.A, 2008), which found that the active ingredients have an anti-fertility effect on mice. High-rate population problems in Indonesia nowadays that increased 1.3 percent per year (BPS, 2007) creating a demand for safe, effective, high-reversibility contraception methods which are not influenced by libido and sexual activity. So, herbal medicine is one of the alternatives to provide family planning methods that meet the requirements. The objective of this research was to find out the influence of prescribing pandan wangi leaves extracts in the depreciation of testicle mass weight and diameter of tubulus. The nature of this research was experimental research using a Posttest Only Control Group Design. Research conducted in the laboratory of the Medical Faculty of Andalas University, starting from July 25, 2008, to August 30, 2008. The population was 24 Japanese's strain mice originated from the Mathematics and Sciences Faculty of was used in analyzing with one control group. ANOVA test was used in analyzing with a degree of significance was 95%, and if the results are significant, then it will be extended with a Bonferroni type Multiple Comparisons test (Post Hoc Test). General results of this research initiate that prescribing the extracts of pandan wangi leaves have influences in the depreciation of testicle mass weight p=0.000, tubulus diameter p=0.001. The null hypothesis is rejected (p < 0.05). Meanwhile, at the Bonferroni Multiple Comparisons test found that statistically, there was no significant influence between groups of treatment. As a conclusion of this research, it was that active ingredients containing in pandan wangi leaves could distract the spermatogenesis process on mice in the depreciation of testicle mass weight and diameter of tubulus. Extension research suggested using different and increased prescribing dosages.